Synthesis, structure and luminescence properties of bifunctional KCaF3 phosphor influenced by incorporating Eu3+ ions for solid state lighting and TL dosimetry applications. (January 2023) - Kameshwaran, R.; Raja, A.; Kumar, R. Ramesh; Daniel, D. Joseph; Annalakshmi, D.O.; Aravinth, K.; Bhargav, P. Balaji; Ramasamy, P.
Abstract: Europium doped KCaF3 phosphors (KCaF3 :Eu 3+ ) were prepared using various concentrations of Eu 3+ by conventional solid-state reaction process. The X-ray diffraction (XRD) studies confirmed the formation of orthorhombic structured KCaF3 :Eu 3+ phosphors. Scanning Electron Microscopy (SEM) image of the synthesized phosphor exhibits agglomerated particles with irregular shapes. The composition of the synthesized sample was determined by Energy Dispersive Spectroscopy (EDS) spectrum and elemental mapping showed the homogeneous dispersion of Eu 3+ ions into the synthesized KCaF3 :Eu 3+ phosphor. The emission peak intensity at 594 nm from photoluminescence (PL) spectra was found to increase with the increase of Eu 3+ concentrations from 0.02 mol% to 0.06 mol% and decreased with the further increase of Eu 3+ concentration up to 0.1 mol%. CIE1931 chromaticity diagram coordinates (x, y) of KCaF3 :(0.06 mol%) Eu 3+ phosphors were positioned in the reddish-orange region (x = 0.5736, y = 0.4224). Photoluminescence property confirms the suitability of KCaF3 :Eu 3+ phosphors for Solid state lighting application. X-ray induced luminescence (radioluminescence, RL) is recorded for KCaF3 :Eu 3+ phosphors showing the characteristic emission of Eu 2+ and Eu 3+ . ESR study on KCaF3 :Eu 3+ phosphors confirm the presence of Eu 2+ ions. Beta irradiated thermoluminescence (TL) glow curve of Eu 3+ doped KCaF3 phosphors is measured and deconvoluted using Gaussian fitting. TL kinetic parameters like activation energy (Ea ) and frequency factor (s) are calculated for all the deconvoluted peaks using peak shape method which shows the synthesized KCaF3 :Eu 3+ phosphors is suitable for dosimetry application. Highlights: Eu 3+ doped KCaF3 phosphors were synthesized by the solid-state reaction method. Structural, morphology and elemental mapping were studied by XRD, SEM and EDAX. Phosphors were characterized via excitation and emission spectra. Activation energy (Ea ) and frequency factor (s) were calculated using peak shape method. Low CCT(⁓1564.73 K) and high CP(95.56%) values could be useful for warm LEDs.